Utilisation of Palm Oil Mill Effluent as Nitrogen Source for Oil Palm (Elaeis Guineensis Jacq.) - Ahamd Tajudin, Mohamad Hashim (1990)
Palm oil mill effluent (POME) is an organic waste material produced at the oil mill. In its raw form, POME is highly polluting. It must be treated before being discharged into the waterways. But in view of its high nutrient content, it can be recycled to the soil as a fertilizer for agricultural crops. In this study, three series of experiments were conducted. First, a laboratory incubation study aimed at determining the rate of nitrogen mineral isation of treated POME. Second, hursery trials with the objective of quantifying the amount of nitrogen availability in treated POME using N-15 tracer technique.